(3CSeGA GdeZJGdjf ef GdGTQGa aj GdLGgdjI hGdGSdGe hCSeGA ef bJd ef GdTYQGA hef ZdHJ cfjJg Ydi GSegs - (3eMeO Hf MHjH Hf CejI Hf YeQh GdgGTej, HGdhdGA, CHh LYaQ GdHZOGOj, ef ehGdj Hfj GdYHGS,J (B245 (3g` s
(3ChdgG (B:s
(3GSeG GdeZJGdjf ef GdGTQGa ai GdLGgdjg hGSeG ef bJd ef GdTYQ hCSeG ef ZdHJ cfjJg Ydi GSeg s
(3BNQgG (B:s
(3Je HMeO Gddg hYhfg HYO JYH TOjO ai cJHg Ydi jO GdabjQ Edi QMeI Gddg JYGdi jhSa Hf eMeO GdTgjQ HGHf Gdhcjd s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B78 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B174s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe LRA (B2/ 1 - (3U (B16 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs